2012
DOI: 10.3109/01612840.2012.718046
|View full text |Cite
|
Sign up to set email alerts
|

Violence against Women in Pakistan: Contributing Factors and New Interventions

Abstract: Pakistan ranks 125th out of 169 countries on the Gender Development Index and has high prevalence rates of Violence against Women (VAW). Contributing factors toward gender based violence at the micro, meso and macro levels include the acceptability of violence amongst both men and women, internalization of deservability, economic disempowerment, lack of formal education, joint family systems, entrenched patriarchal norms and values, and a lack of awareness of legal and other support systems. These factors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…For instance, violence against women can often be quite widespread and can become the "new normal" in some contexts, particularly when the perpetrators themselves were abused and lack power in various domains of their life, which creates a cycle of harm. 71 However, physicians and allied health workers can serve as important catalysts for change to spark community-level shifts in ways of thinking and acting by initiating a dialogue and helping identify local solutions. 72,73 Community engagement is an ongoing process to "create opportunities for community voice and action to affect social and structural conditions that are known to have wide-ranging health effects on communities."…”
Section: What Can Be Done At the Community Level?mentioning
confidence: 99%
“…For instance, violence against women can often be quite widespread and can become the "new normal" in some contexts, particularly when the perpetrators themselves were abused and lack power in various domains of their life, which creates a cycle of harm. 71 However, physicians and allied health workers can serve as important catalysts for change to spark community-level shifts in ways of thinking and acting by initiating a dialogue and helping identify local solutions. 72,73 Community engagement is an ongoing process to "create opportunities for community voice and action to affect social and structural conditions that are known to have wide-ranging health effects on communities."…”
Section: What Can Be Done At the Community Level?mentioning
confidence: 99%
“…However, research from settings as varied as Brazil, Burma, and India has characterised CHWs as trusted members of the community to whom GBV survivors may more readily disclose violence and the need for help (Sarin & Lunsford, 2017;Signorelli et al, 2018;Ved et al, 2019). In Pakistan, GBV survivors experienced positive benefits from group counselling facilitated by CHWs who attended a short training on basic counselling skills (Karmaliani et al, 2012). However, a systematic review by Gatuguta and colleagues (2017) focusing on whether CHWs should offer health services to survivors of sexual violence found that evidence was scanty and of uncertain quality.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Abuse against women happens because abusers have learned to be abusive by watching others in the family and society; abusers have found that it is an effective way of establishing or regaining control; societal attitudes and norms support the use of violence to control others; and powerful gender-based inequalities in society support the notion that woman abuse is a private matter and permit people to look the other way when it happens. 14,17,18 Hence, most of the time, women are more often assaulted by someone known to the family, correspondingly pregnancy does not cause abuse but it is clearly a risk period associated with this. 14,19 The violence is commonly experienced by women at various phases of the life cycle from prenatal period, infancy, childhood, adolescence, reproductive age to old age in different forms.…”
Section: Gender Based Violencementioning
confidence: 99%
“…17,40 One of the main obstacles for women seeking justice is limited, and in some places non-existent support structures for victims of sexual violence. 38,40 Furthermore, the existing legal framework for addressing sexual violence has been criticized by human rights and other organizations as inadequate.…”
Section: Gender-based Violence In the State Levelmentioning
confidence: 99%